Introduction to the symposium on a perfectionist theory of justice by Collis Tahzib - Billingham, P (Taylor & Francis, 2024)
This Introduction summarises some of the central arguments in Collis Tahzib’s important new book A Perfectionist Theory of Justice. It locates Tahzib’s contribution within the wider literature and highlights two distinctive features of his account. First, his incorporation of perfectionist considerations into his theory of justice. And, second, his perfectionist public reason liberalism.